Bamboorigami - Kimura, Junia Shiosawa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Nowadays, the tendency of living in residences with reduced spaces and intimate environments has become not only a necessity, but also an alternative lifestyle. This trend in contemporary society may be refined through multifunctional furniture, implementing innovative, creative and aesthetically differentiated solutions which optimize the utilization of space. In times of concerns with the environment and indiscriminate exploration of the wood industry, bamboo culture reveals itself as a promising material. The plant can be considered an alternative to wooden structures and furniture because of its physical-mecanical properties. Moreover, bamboo is a good atmospheric carbon sequestrator, has a great agricultural potential in soil recovery and is easy to cultivate and manage. The art of folding, as of today, is no longer an exclusive composition made of paper, and it brings its geometric patterns to technological fields, since the application of design objects production until mechanisms developed to the medicine area. This work proposes the development of a multifunctional fitment/furniture, based on the principles of origami folding, so that each of its parts move and fulfill different functions. The material used in this project was glued laminated bamboo-GLB. The multifunctional furniture shown here has performed its proposed functions and has a distinct look by its chosen material. This project's action have mobilized important matters, toward promoting the bamboo culture through the benefits this plant provides to humanity, especially in times of concern about sustainability and [human] quality of life. The origami folding method was projected to the development of this furniture/object, making it versatile and with a unique aesthetics

Atualmente, a tendência de se morar em residências reduzidas e íntimas tornou-se não apenas uma necessidade como também um modo de viver alternativo. Este estilo de vida da sociedade contemporânea pode ser aprimorado por meio dos móveis multifuncionais, com a implementação de soluções inovadoras, criativas e esteticamente diferenciadas, que otimizam a utilização dos espaços. Em tempos de preocupações com o meio ambiente e com a exploração indiscriminada da indústria madeireira, a cultura do bambu tem se revelado muito promissora. Este vegetal pode ser considerado uma alternativa para a produção de madeira para estruturas e mobiliários devido às suas características físico-mecânicas. Além disso, ele é um bom sequestrador de gás carbônico da atmosfera, possui grande potencial agrícola em recuperação de solos e apresenta fácil cultivo e manejo. A arte do origami, vista nos dias atuais, deixa de ser exclusivamente uma composição feita com papel e abrange seus padrões geométricos para áreas da tecnologia, desde aplicação na produção de objetos de design até em mecanismos desenvolvidos para a medicina. O presente trabalho se propôs a desenvolver um móvel multifuncional, com o princípio de dobradura do origami, permitindo que as partes que o compõem movimentem-se para cumprir diferentes funções. O material utilizado foi o bambu laminado colado-BLC. O móvel multifuncional se apresentou cumprindo as funções previstas e com uma aparência diferenciada pela natureza do material em sua procedência. As ações deste projeto mobilizaram questões importantes no sentido de fomentar a cultura do bambu pelos benefícios que esse vegetal proporciona à humanidade, principalmente em tempos de preocupações com a sustentabilidade e qualidade de vida da humanidade. O método de dobradura do origami foi projetado para o desenvolvimento deste mobiliário, tornando-o versátil e com uma estética diferenciada
Keywords: Móveis de bambu; Bambu; Mobiliário; Origami; Bamboo furniture